Advanced turbofan architectures with alternative fuels - Sasi, Sarath (Cranfield University, 2023)
Aviation at present is required to reach net zero carbon emissions by 2050. An effective method to reduce aviation’s carbon footprint with immediate effect is to switch to alternative fuels. This thesis explores novel alternative fuels that could be used for future civil aviation and investigates their impacts on turbofan design to aid in research and development of future turbofan engines operating with alternative fuels. Investigations have been conducted in a systematic manner by adopting an appropriate methodology to answer the identified research questions. The proposed novel alternative fuels for civil aviation consists of seven fuels namely Hydrogen, Ammonia, Methane, DME, Butane, Butanol and Octane with SAF as an additional drop in fuel. The potential impacts and design opportunities for turbofan engines when operating with the proposed alternative fuels is highlighted through a preliminary turbofan design space exploration study. Maximum impacts in the design space are observed for zero carbon fuels Hydrogen and Ammonia. They offer 3% and 6% ESFC benefits respectively against kerosene with up to 20K and 40K peak cycle temperature reduction at take-off. The potential impacts on turbofan engine size and weight when operated by alternative fuels is brought to light through this research. Maximum impacts on engine size, weight and temperature are observed for zero carbon fuels Hydrogen and Ammonia. The maximum benefits in weight and take-off temperatures are 20% and 164K respectively for Ammonia cycles whereas for Hydrogen cycles, it is 6% and 64K respectively. The potential role that aircraft mission range can play in affecting the turbofan engines powered by alternative fuels is showcased in this thesis. Hydrogen SMR and LR aircraft leads to BPR increment up to 31.7% and 61.5% respectively considering a retrofitted style Hydrogen aircraft application.. The potential role of various fuel conditioning strategies and thermal power requirements in affecting turbofan designs highlighted through this research work indicates fuel conditioning to be a major design driver for future turbofan engines operating with alternative fuels. For the investigated LR thrust class application, Hydrogen, Methane and Ammonia requires up to 3 MW, 2.28 MW and 2.2 MW of thermal power to condition the fuel respectively. Finally, the thesis explores the feasibility of utilising Ammonia as a Hydrogen carrier in aviation and highlights certain challenges at mission level and turbofan design implications. For the investigated LR thrust class application, the amount of thermal power required to crack Ammonia into Hydrogen for the Hydrogen turbofan engines can be up to 25 MW which is interestingly an order of magnitude higher than the fuel conditioning requirements of Hydrogen, Methane and Ammonia.
Mourouzidis, Christos - Associate Supervisor
Keywords: engine size; engine weight; temperature; fuel conditioning; aircraft mission range; LR thrust